Cancun update : trade and transfer of technology (International Centre for Trade and Sustainable Development GenevaCH, 2003)
Notes the prospects for Cancun. Provides a background to the topic and notes the mandated deadline. Focuses on the current state of play, highlighting the approaches taken by WTO members. Deals with implementation issues.
Keywords: TRADE NEGOTIATIONS